Salmonella spp. in poultry: a constant challenge and new insights - VELHNER, M.; MILANOV, D.; KOZODEROVIĆ, G. (Journal of the Hellenic Veterinary Medical Society, 2018)
The knowledge about virulence mechanisms, resistance to antimicrobial agents and the biofilm formation ability of Salmonella spp. in poultry industry has been expanded over the years. However, in spite of the research efforts and significant investments to improve management systems in poultry industry, it has become evident that none of the methods applied in all stages of food production chain are 100% effective in eliminating Salmonella spp. Different serovars are manifesting different mechanisms of invasiveness which depend on their ability to invade lower zones of the lamina propria, their ability to gain accesses to parenchymatous organs and survive in macrophages. The ubiquitous nature of Salmonella spp. due to their adaptation to animal and plant hosts, as well as their survival in hostile environments and their enhanced capacity to produce biofilms, contribute to a long lasting contamination of the environment, feed and animals. The emergency and spread of antimicrobial resistances in Salmonella spp. raise additional concerns.